2009
DOI: 10.1590/s0100-40422009000700041
|View full text |Cite
|
Sign up to set email alerts
|

Method validation and stability study of quercetin in topical emulsions

Abstract: . do Café, s/n, 14040-903 Ribeirão Preto -SP, BrasilRecebido em 7/8/08; aceito em 11/3/09; publicado na web em 4/8/09This study validated a high performance liquid chromatography (HPLC) method for the quantitative evaluation of quercetin in topical emulsions. The method was linear within 0.05 -200 µg/mL range with a correlation coefficient of 0.9997, and without interference in the quercetin peak. The detection and quantitation limits were 18 and 29 ng/mL, respectively. The intra-and inter-assay precisions pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…During the study, both emulsions remained physically stable and pH values remained satisfactory, which ensures that F1 and F2 are compatible with the application site, avoiding irritation (24). Regarding functional stability study of DPPH scavenging activity, it was observed that temperature, storage time, and type of formulation influenced the AA of PPE.…”
Section: In Vivo Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…During the study, both emulsions remained physically stable and pH values remained satisfactory, which ensures that F1 and F2 are compatible with the application site, avoiding irritation (24). Regarding functional stability study of DPPH scavenging activity, it was observed that temperature, storage time, and type of formulation influenced the AA of PPE.…”
Section: In Vivo Studiesmentioning
confidence: 82%
“…With the aim of evaluating the physico-chemical characteristics, the following tests were performed: visual evaluation (color, consistence, and phase separation) (24); pH measurement in triplicate (10% dilution in deionized water); evaluation of phase separation in triplicate (2 g of formulation submitted to centrifugation at 145×g for 30 min) (13,25).…”
Section: Evaluation Of Physico-chemical Characteristics Of Formulationsmentioning
confidence: 99%
“…In order to analyze complex samples, such as extract, high performance liquid chromatography (HPLC) is a good tool not only for separating target compounds, but also for revealing the peaks interfering with the analytes. 23 In the 60 years since the first analytical method for quantifying boldine in boldo was published, 24 several other methods using various approaches including densitometry, 25 spectrofluorimetry, 26,27 micellar electrokinetic chromatography, 28,29 voltammetry, 30,31 and LC-NMR have been described. 32 The high performance liquid chromatography (HPLC) method coupled to a UV detector was developed by Pietta et al 33 and this procedure is currently used in different pharmacopoeias for pharmaceutical boldo preparations.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In order to analyze complex samples, such as ointments and creams, high performance liquid chromatography (HPLC) is a good tool not only for separating target compounds, but also for revealing the peaks interfering with the analytes. 21 Moreover, to develop a phytotherapic, it is important to validate an analytical method which presents good performance parameters such as selectivity, linearity, accuracy, precision and recovery over the specified range that an analyte is analyzed. 22 Therefore, the aim of the present work was to develop and validate an HPLC method to quantify SN and SM in a topical formulation and their respective skin penetration.…”
Section: Introductionmentioning
confidence: 99%